(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article discusses the role and methods of games in learning English. This article explores the significance of games in learning English and considers various methods to improve their effectiveness. It highlights the potential of games to engage learners, particularly children and to create a more interesting approach to teaching. Based on wide range of scholarly sources, the article considers the ways in which games assist language learners, act as essential tools for memory retention and foster the growth of communication abilities.